Health risk assessment of metals bound to the fine particulate matter (PM2.5) at Jalan Mahkota, Kuantan - Brendapal Kaur Thind, Jagdiesh Singh (2018)
PM2.5 is respirable particles comprises of complex mixture of very small particles and liquid droplets that contains metals that has ability to penetrate into human body and affect human’s health. Thus, this study was carried out at to determine the concentration of PM2.5 at one of the busiest road in Kuantan city which is Jalan Mahkota. Apart from that, this study aims to determine the concentration of metals bound to PM2.5 and also investigate the meteorological condition such as temperature, wind speed, wind direction and relative humidity which will affect the concentration of metals bound to PM2.5 in the study area. Moreover, the carcinogenic risk and non-carcinogenic risk of metals bound to the PM2.5 is also calculated. The samples of PM2.5 at Jalan Mahkota was collected for the duration of 10 hours using MiniVol Portable Air Sampler. The concentration of PM2.5 is obtained through gravimetric analysis whereas the concentration of metals bound to PM2.5 is analysed using ICP-OES. Then, the carcinogenic risk and non-carcinogenic risk is calculated using formulae adapted from US EPA. The highest concentration of PM2.5 recorded along Jalan Mahkota is 100 μg/m3 whereas the highest concentration of metals bound to PM2.5 is 122.14 ppm. The wind speed and relative humidity greatly influence the concentration of metals bound to PM2.5 along Jalan Mahkota, Kuantan. Based on the health risk assessment table constructed to determine the exposure assessment via inhalation, ingestion and dermal contact of metals bound to PM2.5 at Jalan Mahkota, Kuantan, the study concluded that the carcinogenic risk in acceptable range whereas there is no risk of non-carcinogenic effects. In conclusion, the concentration of metals bound to PM2.5 does not pose any significant health risk to public health at Jalan Mahkota, Kuantan.